Iraqi Universities and Their Social Reform Role in Confronting Extremist Ideology - Abdul-Dulaimi, Assistant Professor Dr. Muhammad Saeed Abdul-Dulaimi; Muhammad, Dr. Abdul-Rahman Salman Muhammad (Sulaimani Journal for Humanities, 2026)
Extremism is a phenomenon that has spread throughout societies of various types, types, and beliefs. It is not linked to a specific environment, society, or religion, even though the West associates it with Islam and presents it to the world as the other face of terrorism, which the West has somewhat succeeded in associating and making a characteristic of Islam. Therefore, it was incumbent upon us to remove this ambiguity and clarify the facts surrounding this concept. We must also clarify the role of educational institutions, especially Iraqi universities, in confronting and confronting such ideas, and how to work to reform society through youth. This is what prompted the researcher to choose to discuss this topic. The youth sector bears the greatest burden in combating this phenomenon and working to reform society, as it is the largest segment of society.
Keywords: Iraqi universities; societal reform; extremist thought